Analisis Sistem Absensi Digital (Mekari Talenta) Karyawan pada PT Hutama Marga Waskita - Mahesa Dimyati Haryo Kasemen; Susan Febriantina; Muhammad Ikhwan (Studi Administrasi Publik dan ilmu Komunikasi, 2025)
In the era of rapid digitalization, the utilization of information technology in human resource management has become increasingly essential. This study examines the implementation of the Mekari Talenta digital attendance system in managing employee attendance administration at PT Hutama Marga Waskita. The objective of this research is to understand the extent of the system's application within the company, identify challenges encountered during its implementation, and explore the strategies employed to overcome these obstacles. Data were collected through interviews, observations, and documentation, involving both primary and secondary sources to gain a comprehensive understanding. The findings reveal that the transition from manual to digital attendance systems presents several challenges, including user negligence in recording attendance, an organizational culture that is not yet fully adaptive to digital systems, and the absence of automatic reminder features. Despite these challenges, the system offers significant benefits such as expediting attendance recap processes, integration with payroll, and providing flexible access to attendance through mobile devices. This research contributes to the existing literature on digital attendance management and provides recommendations for optimizing the use of digital attendance systems in modern workplaces.